ANALISIS INOVASI IDe AsSALAM (Inisiasi Desa Nabung Saham Modal Sampah) DALAM PERSPEKTIF NEW PUBLIC GOVERNANCE - Dinda Novyasari Maharani; Firda Gangsar Ramadanti; Nabila Rasya Annisa (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract Public service innovation in era of rapid development with technology and information that guides local governments to provide improvements in the quality of public services to improving people's welfare. The central government through the Ministry of State Apparatus Empowerment and Bureaucratic Reform (PANRB) is holding the 2022 Public Service Innovation Competition Series (KIPP) as a form of support and encouragement for public service innovation that deserves appreciation. One of the most interesting public service innovations is IDe AsSalam, innovation to save waste as capital stock in improving the local economy. Through the perspective of New Public Governance (NPG), this innovation can be considered as a form of community involvement in decision making and sustainable use of local resources. The purpose of this research to analyzes IDe AsSalam from NPG and discusses challenges faced in implementing innovation. This research used qualitative approach and data were collected through observations with literature review. In the end, IDe AsSalam can be considered as positive innovation and has potential to strengthen community involvement in waste management with sustainable decision-making at the local level. However, to maximize the potential for this innovation requires cooperation and support from various parties, including the government, society and other stakeholders. Keywords: New Public Governance, Public Service Innovation, IDe AsSALAM